Kejawen Clothes Completed With Kromo Javanese Able Preserving the Culture of Courage in the School Environment - Sumiyati Sumiyati; Andayani Andayani; Gunarhadi Gunarhadi (Javanologi: International Journal of Javanese Studies, 2023)
Kejawen clothing is part of the Central Javanese traditional clothing which consists of beskap and kebaya. Beskap is the clothes worn by men and kebaya is the traditional clothes worn by women. The various materials, patterns, and motifs used to make kejawen clothes are able to elevate the wearer's self-image. Kejawen clothing provides a new nuance in education circles in Central Java province which is worn every Thursday starting in 2015. Kejawen is worn by all teachers in schools equipped with Kromo Javanese both to fellow school residents and students during lessons. The Javanese language is currently a language that must be preserved considering that in the technological era, all use millennial languages. The Javanese Kromo language is an innovation carried out by the government in order to preserve eastern culture which prioritizes language politeness traditions. Javanese Kromo language is able to create a realm of communication that provides classification, conditions, socio-cultural background, and individual roles in life. The school environment is an important vehicle for providing real learning from role models regarding polite dress code and polite language procedures for students as the next generation of the nation. This research method uses qualitative, the validation uses theoretical triangulation, the analytical technique used is a qualitative descriptive study with an ethnographic approach. The results show that wearing traditional Kejawen clothing shows pride as a generation in preserving culture. Meanwhile, the use of Kromo Javanese can provide self-confidence, set an example for the next generation in the school environment, be able to adapt and uphold Kromo Javanese as an effort to realize the tradition of language politeness which is fading nowadays.Keywords: Javanese clothing, Kromo Javanese, politeness culture